Nipple Hibernoma in a Dog: A Case Report With Literature Review - Amorim, Irina; Faria, Fatima; Taulescu, Marian; Taulescu, Cristina; Gärtner, Fatima (Frontiers in Veterinary Science, 2021)
This report provides a clinical, histological and immunohistochemical description of an unusual hibernoma (pale cell variant) in the subepidermal area of the nipple of a six-year-old bitch. Furthermore, an extensive literature review of hibernomas in animals was made. Physical examination revealed a nodular lesion in the subepidermal area of the third nipple of the left mammary chain. The histopathological findings included lobules of round to oval cells with abundant pale to eosinophilic cytoplasm, containing one or multiple optically empty vacuoles, consistent with nipple hibernoma. Immunohistochemically, the neoplastic cells were negative for cytokeratin AE1/AE3 and p53 but showed strong immunoreaction for vimentin and uncoupling protein-1, thus confirming the brown adipose tissue origin. Local recurrence was not detected after 18 months of follow-up. Hibernomas are rare and benign neoplastic lesions, originating from brown adipose tissue. Due to their histological and molecular resemblance with liposarcoma, a correct diagnosis of these neoplasms is required. In addition, the literature review suggests that hibernomas may present different features, according to species.